2017
DOI: 10.1038/mi.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protective mucosal immunity mediated by memory Th17 cells against Streptococcus pneumoniae lung infection

Abstract: Pneumonia caused by Streptococcus pneumoniae (Sp) remains a leading cause of serious illness and death worldwide. Immunization with conjugated pneumococcal vaccine has lowered the colonization rate and consequently invasive diseases by inducing serotype-specific antibodies. However, many of current pneumonia cases result from infection by serotype strains not included in the vaccine. In this study, we asked if cross-protection against lung infection by heterologous strains can be induced and investigated the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 50 publications
4
64
0
Order By: Relevance
“…We also demonstrated that this protective immune response is mediated by Th17 CD4 ϩ T cells (19,20). Supporting these findings, another group found that transferred CD4 ϩ T cells from mice that resolved a prior pneumococcal lung infection promote a strong Th17 CD4 ϩ recall response and protect mice against pulmonary challenge with heterologous pneumococcal strains (21). These data suggest the potential use of conserved pneumococcal proteins able to induce a Th17 response that could induce protection against colonization and cooperate against invasive disease.…”
supporting
confidence: 68%
“…We also demonstrated that this protective immune response is mediated by Th17 CD4 ϩ T cells (19,20). Supporting these findings, another group found that transferred CD4 ϩ T cells from mice that resolved a prior pneumococcal lung infection promote a strong Th17 CD4 ϩ recall response and protect mice against pulmonary challenge with heterologous pneumococcal strains (21). These data suggest the potential use of conserved pneumococcal proteins able to induce a Th17 response that could induce protection against colonization and cooperate against invasive disease.…”
supporting
confidence: 68%
“…T H 17 immunity promotes accelerated bacterial clearance in the URT following a secondary infection with S. pneumoniae (144). Considering that type I IFN inhibits T H 17 activation (145) and thus the generation of memory cells, influenza may prevent T H 17mediated protection against subsequent infections with the same or heterologous pneumococcal serotypes (144,187,188).…”
Section: Impact Of Iav-pneumococci Co-infection On Immune Defense At mentioning
confidence: 99%
“…For example, interferon (IFN)-c from CD4 T-cells protects against viral infections, while interleukin (IL)-17 aids controls of bacterial and fungal infections, and IL-4 protects against infection by parasitic worms. [12][13][14][15][16][17][18][19][20] Most immune protection studies are carried out in animal models where challenge studies are feasible and mechanisms of protection can be identified by loss or gain of function. Human challenge studies are, however, becoming more frequent and have also demonstrated that cytokine-producing memory CD4 T-cells correlate with reduced symptoms following pathogen challenge.…”
Section: Cytokine Production Is Key To Cd4 T-cell Protective Immunitymentioning
confidence: 99%